2016
DOI: 10.2903/j.efsa.2016.4437
|View full text |Cite
|
Sign up to set email alerts
|

Safety of the proposed extension of use of acesulfame K (E 950) in foods for special medical purposes in young children

Abstract: Following a request from the European Commission, the EFSA Panel on Food Additives and Nutrient Sources added to Food (ANS) was asked to deliver a scientific opinion regarding the safety of the extension of use of the food additive acesulfame K (E 950) when added to dietary food for special medical purpose (FSMP) intended for young children aged 1-3 years. Acesulfame K was re-evaluated by the European Union (EU) Scientific Committee on Food (SCF) in 2000 who confirmed an acceptable daily intake (ADI) of 9 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…A further seven studies were identified from authoritative sources [70,71,72,73,74,75,76]. These data examined exposure by various EU population groups to all seven sweeteners of interest.…”
Section: Methodology and Trends In Intakementioning
confidence: 99%
See 2 more Smart Citations
“…A further seven studies were identified from authoritative sources [70,71,72,73,74,75,76]. These data examined exposure by various EU population groups to all seven sweeteners of interest.…”
Section: Methodology and Trends In Intakementioning
confidence: 99%
“…These data examined exposure by various EU population groups to all seven sweeteners of interest. Most of the scientific opinions published by the EFSA examined intake in response to requests for extension of use for specific sweeteners considering the total diet [73,74] or in foods for special medical purposes (FSMPs) [75,76]. Acesulfame-K and aspartame have been the most frequently evaluated sweeteners in Europe, with intakes estimated for both sweeteners in 16 different peer-reviewed publications and in one EFSA scientific opinion.…”
Section: Methodology and Trends In Intakementioning
confidence: 99%
See 1 more Smart Citation